If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + 20x = 285 Solving 60 + 20x = 285 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 20x = 285 + -60 Combine like terms: 60 + -60 = 0 0 + 20x = 285 + -60 20x = 285 + -60 Combine like terms: 285 + -60 = 225 20x = 225 Divide each side by '20'. x = 11.25 Simplifying x = 11.25
| (-4x^(4/3))^3/x^(-2/3) | | 3n^6-12=0 | | (3x+-4)*5+36+-4*(15-3x)=10 | | 1/2x+2=3/8x-1 | | 10m-2=0 | | x+6+2x=60 | | 10+5m-7-8m=-15 | | h(t)=-16(1x^2)+16 | | (3x-4)*5+36-4*(15-3x)= | | 2/3y-5/8=2 | | 7.2*1.8= | | 15+7.50=75.00 | | 3x-10x+87=10x+45 | | 0.2(60)+0.05x=-0.1(60+x) | | 33.44=9.95+3.59 | | 2x+8x-149=61 | | 60=0.75x+2.50y | | 16-n=26 | | X+X=3x-6 | | 2.6/1.5= | | 3*(-.5)-((-.5)+1)=6*(-5)+1 | | 5x-3-x+8=2x-7 | | (11x+37)= | | 2/3n=1 | | 5w+3-2w=-21+33w+10 | | -8b-15+5b=11 | | v-3/8=1/8 | | -6fr+13=2f-11 | | T/9-12 | | 1303--1503= | | 5(5+8)=75 | | (20-2x)(40-2x)(x)=784 |